ANALISIS EFEKTIVITAS PENYAMPAIAN SURAT PEMBERITAHUAN WAJIB PAJAK ORANG PRIBADI BERBASIS ONLINE DI KPP PRATAMA TABANAN - Pudja, I Gede Putu Chrisyerio Ananda; Winaya, I Ketut; Wijaya, Komang Adi Sastra (CITIZEN CHARTER, 2023)
Tax submission is the obligation of individual taxpayers to directly and jointly finance the state and national development. One of the efforts of the Directorate General of Taxes in facilitating the submission of annual tax returns is by using the E-filling Program. The Pratama Tabanan Tax Service Office is one of the service offices that has used the E-Filling Program, but even though it has used this program, the number of taxpayers who submit their annual tax returns is still relatively low which does not reach 50% of the number of individual taxpayers registered with the Taxpayer Office. Primary Tax Service Office. This type of research is descriptive qualitative. The results showing that the submission of Taxpayer Tax Returns online is still not fully effective, it can be see from achieving goals and integrity which are experiencing obstacles in terms of funding and socialization, while for adaptation is quite effective. Keywords : Effectiveness, E-Filing, Online Tax Return